W poszukiwaniu tożsamości zarządzania publicznego - Bratnicki, Mariusz; Frączkiewicz-Wronka, Aldona (In search identity public management, 2006)
The main issue touched upon in this article is need of reappraisal of management sciences area. It is an effect of changes which are occurring nowadays. Both State and state machinery more are more often use management methods and tools typical for market sector in decision making process in the public and social sector.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 63-72